Study on Estrogen Receptor, Progesterone Receptor and HER-2/ neu Expression Pattern by Immunohistochemistry in 87 cases of Invasive Breast Cancer - Hossain, Md Shahadat; Begum, Ferdousy; Barua, Ashim Ranjan (KYAMC Journal, 2017)
Background: Now a day's determination of estrogen receptor (ER), progesterone receptor (PR) and HER-2/neu expression pattern by immunohistochemistry in invasive breast cancer have become the standard procedure for breast cancer management. Objective: To see the expression pattern of estrogen receptor, progesterone receptor and HER-2/neu in Bangladeshi women with invasive breast carcinoma. Method: This cross sectional study was performed in 87 cases of invasive breast cancer. Estrogen receptor (ER), Progesterone receptor (PR) and HER-2/neu expression pattern were assessed by immunohistochemistry using monoclonal antibodies for detecting estrogen and progesterone receptors, and polyclonal antibody for detecting HER-2/neu. Results: All the cases were graded according to Bloom-Richardson grading system. Of those, Grade I tumour was 18 (20.69%), Grade II tumour was 58 (66.67%) and Grade III tumour was 11(12.64%). Both ER and PR positive reactivity were same and it was found 65 (74.71%) and HER-2/neu reactivity pattern were found negative in 59 (67.82%) cases and positive in 28 (32.18%) cases. A statistically significant correlation was found between the expression of ER and low grade tumour (p=0.011) and combined estrogen and progesterone receptor positive reactivity with low grade tumour (p=0.002). Conclusion: ER, PR and HER-2/neu expression do not correlated with each other, so it is recommended that each test should be independently determined by immunohistochemistry in all cases of invasive breast cancer. All equivocal cases of HER-2/neu (score 2+) should be analyzed by FISH technique to find out the percentage of real score. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 436-443